Enhanced Biogas Production via Anaerobic Digestion of Organic Waste with Rice Water: Methane Yield and Substrate Interactions - Sudarman,; Hendaryati, Roro Heni; Soegiharto, Achmad Fauzan Hery; Ismail, Dyanu Moulana; Ramadhan, Rizki Raihan; Nugroho, Willy Satrio; Sofi'i, Yepy Komaril (International Journal of Integrated Engineering, 2026)
The increasing global energy crisis, driven by the overexploitation of fossil fuels, has necessitated the development of renewable energy sources. Biogas, produced through anaerobic digestion of organic waste, presents a promising alternative. This study investigates the potential of enhancing methane production and gas concentration by incorporating rice water as a fermentation accelerator in organic waste mixtures, including fruits (Artocarpus heterophyllus), vegetables (Lactuca sativa), and grass (Cenchrus purpureus). The organic waste was characterized using Fourier Transform Infrared Spectroscopy (FTIR), X-ray Diffraction (XRD), and Scanning Electron Microscopy with Energy Dispersive X-ray Spectroscopy (SEM-EDX) to understand the molecular interactions during fermentation. Experimental methods were employed, utilizing a custom-built biogas reactor. The organic waste was mixed with rice water in varying compositions and subjected to anaerobic fermentation. The results indicate that the combination of jackfruit and lettuce produced the highest methane yield and gas concentration, followed by jackfruit alone, while grass and lettuce yielded lower methane concentrations. Molecular analysis revealed that the high carbohydrate content in the rice water significantly accelerated the decomposition process, thereby enhancing methane production. This study demonstrates that the strategic combination of specific organic wastes with rice water can optimize biogas production, offering a sustainable solution to energy needs and waste management challenges. The findings contribute to the body of knowledge on biogas production and suggest practical applications for improving the efficiency of methane generation from organic waste.